2004
DOI: 10.1007/s00122-004-1665-1
|View full text |Cite
|
Sign up to set email alerts
|

QTL controlling root and shoot traits of maize seedlings under cold stress

Abstract: The improvement of early vigour is crucial for the adaptation of maize (Zea mays L.) to the climatic conditions of central Europe and the northern Mediterranean, where early sowing is an important strategy for avoiding the effect of summer drought. The objectives of this study were to identify quantitative trait loci (QTL) controlling cold-related traits and to investigate the relationships among them. A set of 168 F 2:4 families of the Lo964 × Lo1016 cross was grown in a sandvermiculite substrate at 15/13°C (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 29 publications
12
108
4
Order By: Relevance
“…When an LRT was used to determine the overall significance of the epistatic interactions for all six traits evaluated in this study, the tests indicated that the model with epistasis significantly fit the data better (Po0.01) than the reduced model without epistatic interactions. The importance of the QTL by density interaction is consistent with results from other whole-genome scan studies on plant response to stress such as nitrogen deficiency (Bertin and Gallais, 2001;Hirel et al, 2001), water deficiency (Landi et al, 1995;Ribaut et al, 1996; (Reiter et al, 1991), and cold temperature growing conditions (Hund et al, 2004). Physiological response to stress in general may be similar as response to density stress and enhanced tolerance to crowding may confer enhanced tolerance to other stresses.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…When an LRT was used to determine the overall significance of the epistatic interactions for all six traits evaluated in this study, the tests indicated that the model with epistasis significantly fit the data better (Po0.01) than the reduced model without epistatic interactions. The importance of the QTL by density interaction is consistent with results from other whole-genome scan studies on plant response to stress such as nitrogen deficiency (Bertin and Gallais, 2001;Hirel et al, 2001), water deficiency (Landi et al, 1995;Ribaut et al, 1996; (Reiter et al, 1991), and cold temperature growing conditions (Hund et al, 2004). Physiological response to stress in general may be similar as response to density stress and enhanced tolerance to crowding may confer enhanced tolerance to other stresses.…”
Section: Discussionsupporting
confidence: 85%
“…Such studies have provided insights into the genetic architecture of plant response to nitrogen deficiency (Bertin and Gallais, 2001;Hirel et al, 2001), water deficiency (Landi et al, 1995;Ribaut et al, 1996;Tuberosa et al, 1998;Sanguineti et al, 1999;Sari-Gorla et al, 1999;Tuberosa et al, 2002;Li et al, 2003), low phosphorus (Reiter et al, 1991), and cold temperature growing conditions (Hund et al, 2004). Although these studies clearly showed an interaction between QTL and stress, they identified QTL for response to stress indirectly by mapping the trait of interest (that is yield) under two or more conditions and overlaying the resulting scans on the common map, to identify shared and distinct QTL.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on QTL mapping for chlorophyll have been reported and a large number of QTLs have been identified on 10 maize chromosomes using different mapping populations including subjected to normal and adverse environments (Hund et al, 2004;Jompuk et al, 2005;Messmer, 2006;Trachsel et al, 2010;Zaidi et al, 2015). Hund (2004) conducted genetic mapping in F2:4 from a Lo964 × Lo1016 cross under cold stress and discovered seven QTLs for SPAD value at chromosomes 1, 3, 4, 5 and 10. Jompuk et al (2005) also reported 10 QTLs that were responsible for SPAD values of the third leaf of maize seedlings under different times of sowing in one F2:3 population and three of these on chromosomes 1, 3 and 10 Marker: closest marker to the QTL position.…”
Section: Discussionmentioning
confidence: 99%
“…In the F 2:4 population of maize, forty QTLs were identifi ed under cold stress were associated with the shoot, root and seed traits. The QTLs effects ranged from 0.4 to 30.1% (9).…”
Section: Resultsmentioning
confidence: 99%